Alih Kode dan Campur Kode pada Lirik Lagu “Ramadan” dan “Eidun Saeed” Karya Maher Zein - Fathonah, Azzahra Ismi; Kulsum, Umi; Sa’adah, Rd. Siti; Nugraha, Mugy; Nugroho, Rafly Sutan (Study Program of Arabic Language Teaching, 2025)
This study investigates the forms and functions of code-switching and code-mixing found in Maher Zain’s songs Ramadan and Eidun Saeed, which combine English and Arabic as part of a global religious musical expression. The research aims to identify and classify types of code-switching based on Poplack’s framework and types of code-mixing according to Muysken’s typology, and to understand the sociolinguistic motivations behind their use. Employing a qualitative descriptive method, the data were collected through a close Reading of the official song lyrics available on digital music platforms. The analysis reveals that inter-sentential switching is the most dominant form in both songs, particularly noticeable in the transition between English verses and Arabic choruses. Code-mixing primarily takes the form of insertion, with Arabic lexical items embedded in English sentence structures to maintain religious authenticity and evoke spiritual nuance. The findings indicate that the multilingual style in these songs is not merely decorative but serves important communicative, aesthetic, and cultural purposes. Overall, this study concludes that Maher Zain’s use of language alternation functions as a strategy to strengthen religious meaning and connect diverse listeners across linguistic and cultural backgrounds.